Persepsi Mahasiswa UPN Veteran Jatim Terhadap Akun Instagram DPD PSI Surabaya - Choirul Anshor AR; Rastra Airlangga P; Jhaka Sena; Dyva Claretta (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
The party is one embodiment of a form of democracy. This is due to the function of political parties which are a form of bridge for people's aspirations and at the same time a mirror of the political level in society. This is one of the concrete manifestations of the democratic leadership of the Indonesian state, which means that the highest power is in the hands of the people. In the political parties in Indonesia, many parties are now emerging. One of them is PSI. PSI is an abbreviation of the Indonesian Solidarity Party. PSI is one of the political parties that takes advantage of the development of social mrfia, one of which is Instagram. In this study, the research object studied was the Instagram account of the DPD PSI Surabaya (@psi_surabaya). This study aims to determine the perceptions of UPN Jatim students towards the Instagram account @psi_surabaya in forming a positive image of the party through social media.